KEPASTIAN HUKUM DALAM PENGADAAN TANAH UNTUK PEMBANGUNAN PROYEK STRATEGIS NASIONAL TERKAIT GANTI KERUGIAN BAGI MASYARAKAT YANG TERDAMPAK - Aditya, Muhammad Irfan; Maryano, Maryano; Yani, Ahmad (SENTRI: Jurnal Riset Ilmiah, 2023)
Procurement of land for development is carried out through deliberation between the parties in need of land and land rights holders. Law No. 5 of 1960 on basic agrarian principles regulation (UUPA) was established to regulate public relations with land and provide legal certainty. Article 18 of the UUPA and Law No. 2 of 2012 on the acquisition of land for development in the public interest regulates the release of land rights by providing reasonable compensation. However, in practice, compensation problems often arise in development projects such as the Cisumdawu Toll Road and the Cibitung-Cilincing Toll Road, which indicate obstacles in securing community rights to land affected by development. The formulation of the problem in this study is how the implementation of compensation for the community against the acquisition of land in the national strategic project? And how is the legal certainty related to land procurement in national strategic projects related to legislation on land procurement and job creation laws? The theory used in this study is the theory of legal certainty according to Jan Michael Otto. The method used in this study with the type of normative juridical research in the form of legal material literature or secondary data with sources of primary, secondary and tertiary legal materials. The research approach that used the approach of legislation, conceptual, analytical and case and collection techniques of legal material is done by identifying and inventorying the rules of positive law, literature books, journals and other sources of legal materials. For technical analysis of legal material is done by the interpretation of systematic and grammatical laws. The results showed that the implementation of compensation for the community against land acquisition in national strategic projects has its own challenges and complexities. The process of determining the amount of damages should consider aspects of eligibility and fairness for land rights holders. Legal certainty related to land acquisition in national strategic projects is very important to avoid conflict and uncertainty for all parties concerned. Changes in the legislation on land acquisition and the implementation of the job creation law have provided a number of efforts to increase legal certainty in the process. For this reason, the government needs to adopt an inclusive approach to ensure fairness in compensation related to land acquisition and the need for regular monitoring and evaluation of the implementation of regulations on a regular basis so as to identify obstacles that arise and allow for the necessary improvements